Inovasi Pemadam Kebakaran Dan Sistem Alarm Berbasis Arduino Menggunakan Smartphone Dengan Metode TRIZ - Kurniawan, Dani Dwi; Riyanto, Ong Andre Wahyu; Ismantoko, Mohammad Fahrul Ansori; Hariyanto, Krisnadhi; Dewi, Fitriya Gemala; Subaderi, Subaderi (Journal of System Engineering and Technological Innovation, 2023)
Many fire incidents that happened in settlement area kabupaten gresik , the researcher would willing to develop a small scale detection and firemen that monitored by smartphone. This system uses microcontroller arduino with teoriya resheniya izobreatatelskikh zadatch ( triz ) analysis. Methodology used in this research choose aim , gather field literature study and fiels observation. Spread questionnaire to 80 respondents. Analyze validity and reliability of questionnaire result. Continued by the manufacture and selection prototype design them process of making the prototype of design elected. The final stage of research is done testing physical and functions of the produced prototype. This prototype uses fire sensor DFR 0076 and furnished with gas sensor MQ2 and temperature sensor NTC Thermal Sensor. It comes with some features, Bluetooth, hydrant pump and smartphone Aplication. This Prototype tested and functioning well.